Al-Razi's understanding and curing of smallpox and measles - Hawari, Iman; Daoud, Jamal Ibrahim (IIUM Press, 2011)
The objective of this study is an attempt to introduce the role of the Muslim scholar, namely AI-Razi, in establishing treatment for smallpox and measles clinical observations. The methodology of this chapter uses the book written by AI-Razi about smallpox and measles in Arabic language as a reference. In 1970, the World health Organization (WHO) praised AI-Razi for the originality and accuracy in his writings in this subject (Amoozaneh & Ashtiyani, 2010). Smallpox and measles have been known through the decades as prominent killers destroying millions of lives as they pass through towns and villages, though vaccines for both diseases were developed